Color-induced cognitive conflicts affect muscle activity prior to gait initiation in the Go/No-go task - Horinouchi, Takayuki; Ishida, Haruki; Yang, Kangjing; Li, Jingnan; Morishita, Takuya; Watanabe, Tatsunori; Kirimoto, Hikari (Frontiers in Human Neuroscience, 2024)
In traffic rule, green/blue means go, and red means stop. It has been shown that this prior knowledge about traffic signal colors can affect reaction times (RTs). For example, RTs are longer when responding to a red "Go" signal and withholding the response to a blue "No-go" signal (Red Go/Blue No-go task) than when responding to a blue "Go" signal and withholding the response to a red "Nogo" signal (Blue Go/Red No-go task), when responses are provided by button press. However, it remains unknown whether this holds in different actions. The aim of this study was to investigate the effect of prior knowledge of color on gait initiation in a Go/No-go task. Seventeen participants performed Green Go/Red No-go and Red Go/Green No-go tasks, in which they stepped forward from a force plate in response to a green or red signal and withhold the response to red or green signal, respectively. We recorded the center of pressure (COP) and electromyogram (EMG) from the bilateral tibialis anterior muscles during gait initiation. The onset of COP movement and toe-off time as well as COP displacements did not differ between the Go/No-go tasks. The EMG onset for the stance leg was delayed in the Red Go/Green No-go than Green Go/Red No-go task. These findings suggest that the conflict between prior knowledge of color related to traffic rule and the meaning of the stimulus color affects muscle activity but not COP characteristics during gait initiation, highlighting two distinct motor control mechanisms, where the initial phase is influenced by cognitive load while the subsequent phase remains unaffected. This dissociation suggests that the later phase of gait initiation relies on robust spinal loops and central pattern generators, which are less influenced by cognitive factors such as prior knowledge.